Prognostic impact of KRAS mutation status for patients with stage IV adenocarcinoma of the lung treated with first-line pembrolizumab monotherapy. (May 2021) - Noordhof, A.L.; Damhuis, R.A.M.; Hendriks, L.E.L.; de Langen, A.J.; Timens, W.; Venmans, B.J.W.; van Geffen, W.H.
Highlights: The overall survival of KRAS mutated versus KRAS wild-type NSCLC patients with PD-L1 ≥ 50 % is similar, when treated with first-line pembrolizumab. KRAS has no prognostic value with respect to treatment with pembrolizumab in stage IV lung adenocarcinoma patients with PD-L1 ≥ 50 %. In this selected cohort with PD-L1 ≥ 50 % and excluded other mutations, KRAS mutations are more frequently seen in women than in men. Abstract: Objectives: Monotherapy with pembrolizumab is the preferred first-line treatment for metastatic non-small cell lung cancer with programmed death-ligand 1 (PD-L1) expression ≥50 %, without targetable oncogenic drivers. Although targeted therapies are in development for patients with specific Kirsten rat sarcoma ( KRAS ) mutations, these are not available in daily care yet. It is not clear whether there is a difference in survival on first-line pembrolizumab for patients with a high PD-L1 status with or without a KRAS mutation. We aim to compare this survival based on real-world data. Materials and methods: This is a real-world retrospective population-based study using data from the Netherlands Cancer Registry. We selected patients with stage IV lung adenocarcinoma with PD-L1 expression ≥50 % diagnosed between January 2017 and December 2018, treated with first-line pembrolizumab. Patients with EGFR mutations, ALK translocations or ROS1 rearrangements were excluded. The primary outcome parameter was overall survival. Results: 388 (57 %) of 595 patients had a KRAS mutation. KRAS was seen more frequently in women than in men (65 % versus 49 % respectively, p < 0.001). The median overall survival was 19.2 months versus 16.8 months for patients with and without KRAS mutation, respectively (p = 0.86). Multivariable analysis revealed WHO performance score, number of organs with metastases and PD-L1 percentage as independent prognostic factors. KRAS mutation status had no prognostic influence (hazard ratio = 1.03, 95 % CI 0.83−1.29). Conclusion: The survival of KRAS mutated versus KRAS wild-type lung adenocarcinoma patients, treated with first-line pembrolizumab monotherapy, is similar, suggesting that KRAS has no prognostic value with respect to treatment with pembrolizumab.